STRUGGLE FOR GETTING TRUE LOVE IN MR AND MRS SMITH MOVIE:AN INDIVIDUAL PSYCHOLOGICAL APPROACH - YUNARI, DWI (2010)
The major problem of this study is struggle for getting true love of Jane Smith reflected in Mr. and Mrs. Smith movie. The objectives of the study are to analyze the structural elements of the movie and to analyze the main character of Jane Smith based on individual psychological perspective. In conducting this study the researcher uses qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is from Mr. and Mrs. Smith movie directed by Doug Liman released in 2004. While the secondary data sources are other materials taken from books, scripts, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the analysis shows the following conclusions. Firstly, structural approach is used to analyze the elements of the movie. It consists of characterization, setting, plot, point of view, theme, message, cast, mise- en- scene, sound, editing, cinematography, style, and design. Secondly the individual psychological approach is used for analyzing character of Jane Smith that for getting true love. These approaches are applied in order to get the appropriate analysis and answer the problem of the research. .